Neuropharmacological studies of antidepressant action on brain dopamine systems - Ainsworth, K; Ainsworth, Kerri (1998)
There is compelling evidence to suggest that several core symptoms of severe depressive illness (anhedonia, loss of motivation and psychomotor retardation) arise as a consequence of abnormal neurotransmission within the mesocorticolimbic system. Moreover, changes in transmitter function within this circuitry are thought to contribute to the therapeutic effect of antidepressant treatments. A key output station of the mesocorticolimbic system is the nucleus accumbens. This nucleus utilizes dopamine as one of its main neurotransmitters and is closely associated with both reward and psychomotor behaviour. This thesis investigated, in the rat, the effect of antidepressant drugs on central dopamine function, primarily within the nucleus accumbens. Several neuropharmacological techniques were employed; dopamine receptor function was studied using behavioural methods, dopamine receptor expression was measured using in situ hybridization and receptor autoradiography, and dopamine release was monitored using in vivo microdialysis. Behavioural data revealed that antidepressant drugs from differing generic groups selectively enhanced the function of dopamine D2-like (i.e. D2, D3 and D4) but not Dl-like (i.e. D1 and D5) receptors. Specifically, repeated (but not acute) administration of fluoxetine, sertraline, desipramine and tranylcypromine was found to enhance the behavioural response (predominantly locomotor activation) to D2-like (quinpirole and RU 24213), but not Dl-like (SKF 38393 and SKF 81297), dopamine receptor agonists. Neurochemical experiments established that repeated administration of fluoxetine, sertraline, desipramine and tranylcypromine increased D2 (but not D1) receptor mRNA levels within the nucleus accumbens, most notably in the shell subregion. Subsequent receptor autoradiography experiments revealed that fluoxetine, sertraline and desipramine (but not tranylcypromine) also increased D2-like (most probably D2) binding site density in this region. In vivo microdialysis experiments established that fluoxetine, sertraline and desipramine (when administered repeatedly) had no effect on extracellular dopamine in the nucleus accumbens, whilst tranylcypromine caused a marked increase. Thus, the antidepressant-induced increase in accumbens D2 receptor expression is unlikely to be an adaptive response to decreased dopamine release. Interestingly, in a final series of experiments, subchronic administration of the direct acting 5-HT2 agonists, DOI and DOB (but not mCPP), was found to enhance the behavioural response to D2-like, but not Dl-like, receptor agonists. In addition, DOI was also found to increase D2(but not D1) mRNA and D2-like binding site density in the nucleus accumbens. Together, these data suggest, at least in the case of fluoxetine and sertraline, that the increase in D2-like receptor function and D2 receptor expression may be triggered by activation of 5-HT2 (possibly 5-HT2A) receptors. Overall, data presented in this thesis suggest that the antidepressants tested enhance dopamine function in the nucleus accumbens through either increased expression of postsynaptic D2 receptors (fluoxetine, sertraline and desipramine) or increased dopamine release (tranylcypromine). These findings raise the exciting and novel possibility that increased dopamine function within the nucleus accumbens may play a key role in the therapeutic effect of these, and possibly other, antidepressant treatments.